2023
DOI: 10.1007/s00018-023-04887-5
|View full text |Cite
|
Sign up to set email alerts
|

Collagen VI sustains cell stemness and chemotherapy resistance in glioblastoma

Abstract: Microenvironmental factors are known fundamental regulators of the phenotype and aggressiveness of glioblastoma (GBM), the most lethal brain tumor, characterized by fast progression and marked resistance to treatments. In this context, the extracellular matrix (ECM) is known to heavily influence the behavior of cancer cells from several origins, contributing to stem cell niches, influencing tumor invasiveness and response to chemotherapy, mediating survival signaling cascades, and modulating inflammatory cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Other studies have identified COL11A1 as a functional driver of cancer progression and prognostic biomarker [108][109][110]. A similar body of the literature is emerging supporting pro-tumourigenic functions for COLVI in breast, ovarian [111], pancreatic [112], lung [113], and brain [114] cancers. Clinical intervention here is yet to be explored.…”
Section: Is Tumour Fibrosis Good or Bad?mentioning
confidence: 84%
“…Other studies have identified COL11A1 as a functional driver of cancer progression and prognostic biomarker [108][109][110]. A similar body of the literature is emerging supporting pro-tumourigenic functions for COLVI in breast, ovarian [111], pancreatic [112], lung [113], and brain [114] cancers. Clinical intervention here is yet to be explored.…”
Section: Is Tumour Fibrosis Good or Bad?mentioning
confidence: 84%
“…Some components of the extracellular matrix can affect the recruitment of monocytes/macrophages [ 115 , 116 ]. Spondin 2 (SPON2), a matricellular protein 2, is essential for recruiting lymphocytes and initiating immune responses, as well as having a role in tumor progression [ 117 , 118 ].…”
Section: Re-education Of Tam Towards the Anti-tumor Phenotypementioning
confidence: 99%
“…Among the different collagen subtypes expressed in glioma, collagen VI was reported to be overexpressed in GBM and high-grade glioma when compared to lower-grade astrocytoma and normal glia (Fujita et al 2008 ). Collagen VI is composed of three different subunits, α1(VI), α2(VI), and α3(VI), whose overexpression in GBM relapses has been related to increased DNA repair and cell survival in response to both radio- and chemotherapy (Cescon et al 2023 ). The aberrant activation of pro-survival signaling pathways including DNA replication and repair genes by collagen VI favor the development of pro-malignant cell behavior in GBM and negatively impact on GBM patients’ prognosis (Cescon et al 2023 ).…”
Section: Ecm Molecules In Aatsmentioning
confidence: 99%
“…Collagen VI is composed of three different subunits, α1(VI), α2(VI), and α3(VI), whose overexpression in GBM relapses has been related to increased DNA repair and cell survival in response to both radio- and chemotherapy (Cescon et al 2023 ). The aberrant activation of pro-survival signaling pathways including DNA replication and repair genes by collagen VI favor the development of pro-malignant cell behavior in GBM and negatively impact on GBM patients’ prognosis (Cescon et al 2023 ). In particular, collagen VI deposition has been correlated with the enhanced invasion associated with resistance to bevacizumab (Cha et al 2023 ).…”
Section: Ecm Molecules In Aatsmentioning
confidence: 99%